Removal of bismuth ions utilizing pillared ilerite nanoclay: Kinetic thermodynamic studies and environmental application - Salam, Mohamed Abdel; Alshehri, Abdulmohsen A.; Schwieger, Wilhelm; Mokhtar, Mohamed (Microporous and Mesoporous Materials, 2020)
It is very important to purify and remediate the environment by removing the heavy metals such as bismuth. Herein, Na-ilerite nanoclay was prepared and then treated to produce SiO2 pillared ilerite. For exploring the morphological structure, functional groups, and surface area of the ilerite before and after pillaring, different characterization techniques were used; scanning electron microscope (SEM), X-Ray diffraction (XRD), FT-IR, and surface area analysis solid. The prepared pillared ilerite nanoclay was used as an adsorbent for removing Bi(III) from model solution, and environmental samples. The characterization results indicates the pillaring of the ilerite nanoclay, and the great enhancement in the specific surface area of the ilerite upon pillaring from 45.0 m2 g−1 to 582 m2 g−1. The effects of pillared ilerite nanoclay mass, adsorption time, solution pH, ionic strength, and temperature on the removal of Bi(III) had been explored. The optimum removal capacity of pillared ilerite obtained was about 139.9 mg Bi(III)/g using 0.02 L of 100 mg L−1 Bi(III) solution, and pillared ilerite 5.0 mg within 60.0 min, at pH 2.0, and 298 K. Bi(III) ions removal by pillared ilerite was studied kinetically as well as thermodynamically, and the findings showed the pseudo-second-order kinetic model suitability, electrostatic, endothermic, chemical, and spontaneity nature of the removal process. Moreover, pillared ilerite nanoclay could be used for three consecutive times for the efficient removal of Bi(III) with high efficiency. Finally, the pillared ilerite nanoclay applicability for removal of Bi(III) in different spiked Red Sea water, waste water, and tap water sample was investigated and the pillared ilerite nanoclay showed a great potential application to removing Bi(III) from the environment.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Bismuth ion; Kinetics; Nanoclay; Pillared ilerite; Thermodynamics; Water treatment